A Novel Single-Source 13-Level Switched- Capacitor Inverter With Triple Voltage Gain - Kyrmyzy Taissariyeva; Murat Karakilic; Kuanysh Mussilimov; Hasan Hatas (IEEE Access)
In recent years, the growing demand for efficient voltage boosting solutions has been driven by advancements in renewable energy systems, electric vehicles (EVs), and photovoltaic (PV) arrays. However, conventional magnetic-based inverters remain bulky and inefficient for compact, high-performance applications, limiting their use in emerging technologies. To address this, the objective of this study is to develop a compact, single-source switched-capacitor multilevel inverter (SC-MLI) topology that achieves high voltage gain with minimal component count. The proposed 13-level SC-MLI employs a novel switched-capacitor structure and is evaluated under Natural Level Control (NLC) and Sinusoidal PWM (SPWM) schemes. Theoretical analysis, MATLAB/Simulink simulations, and experimental validation on a 100–1000 W prototype are carried out, along with thermal modeling in PLECS. The results show that the topology achieves a voltage gain of 3, maintains capacitor self-balancing without auxiliary circuits, and reaches a peak efficiency of 97.2% (simulation) and 95.3% (experiment). Moreover, it meets harmonic standards, reduces total harmonic distortion (THD), and outperforms recent single-source designs in terms of accuracy, cost, and control simplicity. This makes the proposed topology highly suitable for grid-connected PV systems, electric vehicle chargers, and compact renewable energy interfaces, with theoretical scalability toward medium- and high-power applications.